Integrating SLAM LiDAR, UAV-LiDAR, and orbital remote sensing to quantify passive forest regeneration in the Brazilian Cerrado - Rômullo Oliveira Louzada; Diego Campos Vasconcelos; Gabriel Ferreira da Silva; Fernanda Vitorio Vieira; Junior da Silva Camargo; Maximiliano Guimarães Sales Sales; Fernando Hentschke; Ivan Rodrigo Leonardi; Thiago Gentil Ramires (Remote Sensing Applications: Society and Environment, 2026)

Ocular microtremor: a structured review - Lisa Graham; Julia Das; Rodrigo Vitorio; Claire McDonald; Richard Walker; Alan Godfrey; Rosie Morris; Samuel Stuart (Experimental Brain Research, 2023)
Ocular microtremor (OMT) is the smallest of three involuntary fixational micro eye movements, which has led to it being under researched in comparison. The link between OMT and brain function generates a strong rationale for further study as there is potential for its use as a biomarker in populations with neurological injury and disease. This structured review focused on populations previously studied, instrumentation used for measurement, commonly reported OMT outcomes, and recommendations concerning protocol design and future studies. Current methods of quantifying OMT will be reviewed to analyze their efficacy and efficiency and guide potential development and understanding of novel techniques. Electronic databases were systematically searched and compared with predetermined inclusion criteria. 216 articles were identified in the search and screened by two reviewers. 16 articles were included for review. Findings showed that piezoelectric probe is the most common method of measuring OMT, with fewer studies involving non-invasive approaches, such as contact lenses and laser imaging. OMT frequency was seen to be reduced during general anesthesia at loss of consciousness and in neurologically impaired participants when compared to healthy adults. We identified the need for a non-invasive technique for measuring OMT and highlight its potential in clinical applications as an objective biomarker for neurological assessments. We highlight the need for further research on the clinical validation of OMT to establish its potential to identify or predict a meaningful clinical or functional state, specifically, regarding accuracy, precision, and reliability of OMT.

Imputation accuracy for genomic selection using embryo biopsy samples in Gir - Clara Slade Oliveira; Marcos Vinicius Gualberto Barbosa da Silva; Carolina Capobiango Quintão; Pamela Itajara Otto; Rodrigo Vitorio Alonso; Luiz Fernando Feres; João Claudio do Carmo Panetto; Marco Antonio Machado; Luiz Sergio de Almeida Camargo (Reproductive Biology, 2023)